Somali diaspora’s remittances cast a life line - United Nations (Africa Renewal, 2013)
During two decades of conflict, famines and floods, money sent back home by Somali expatriates — known as remittances — has been instrumental in keeping Somalia afloat. The UN Development Programme estimates that 1.6 billion in remittances is sent back annually by Somali emigrants living in North America and Europe. Abdirashid Duale, a Somali who is chief executive of Dahabshiil, one of the largest money-transfer businesses in Africa, says that such transfers have been “a lifeline” for Somalis.